Deslizamientos en el barrio Fausto Bazante y los factores que influyen en la vulnerabilidad. Periodo mayo – septiembre 2023. - Ocampo Arguello, Jessica Gisela (2023)
This study focuses on evaluating and recommending landslide risk prevention and mitigation measures in the Fausto Bazante area of Guaranda. The fundamental challenges are linked to the lack of available information, insufficient institutional cooperation, inadequate records, and limitations in historical rainfall and gradient information. The purpose is to identify risk factors, assess probability, create hazard models and propose prevention and mitigation measures. Potential achievements include reducing the impact and vulnerability of people to landslides. The method employed combines qualitative and quantitative approaches to collect and analyze data. The study has faced considerable challenges due to the lack of complete information, which hinders the analysis and assessment of risk in the Fausto Bazante area. Also, the lack of institutional cooperation has hindered access to crucial data and complicated the implementation of preventive and corrective measures. To address these limitations, qualitative and quantitative methods are applied. Information is collected from a variety of sources and both qualitative and quantitative analytical methods are used. This allows identifying key risk factors, assessing the probability of sizes and simulating risks in the study area. The main objective is to implement effective prevention and mitigation measures to reduce the risk of gradual increases and increase the resilience of the community. These measures will be based on the results of a risk and vulnerability analysis, taking into account the factors identified and the specific conditions of the Fausto Bazante. Key words: deslizamientos, Prevención, Mitigación, Riesgo, resiliencia, Evaluación.